1995
DOI: 10.1145/203356.203365
|View full text |Cite
|
Sign up to set email alerts
|

Apprenticing with the customer

Abstract: A new computer system changes how its customers work. Designing such a system requires indnrate knowledge of customers' wor"k and motives to ensure that the system supports them well. The creation of a new system implicitly means designing the new work practice it will support.Because .system design is so intimately involved with how people work, designers need better approaches to gathering customer requirements.' The current interest in participatory design, ethnographic techniques, and field research techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(72 citation statements)
references
References 7 publications
0
65
1
6
Order By: Relevance
“…Our primary situated data gathering technique was the use of contextual interviews, as described by Beyer & Holtzblatt (1995) and Holtzblatt & Jones (1993). In a contextual interview the investigator observes the interviewee carrying out his or her normal work.…”
Section: Contextual Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our primary situated data gathering technique was the use of contextual interviews, as described by Beyer & Holtzblatt (1995) and Holtzblatt & Jones (1993). In a contextual interview the investigator observes the interviewee carrying out his or her normal work.…”
Section: Contextual Interviewsmentioning
confidence: 99%
“…Holtzblatt and colleagues have developed a methodology, called contextual inquiry (Holtzblatt & Jones, 1993;Beyer & Holtzblatt, 1995;Holtzblatt & Beyer, 1996), which provides a number of techniques for studying work context. The need to study the context of work is also evident in the popularity of broadly ethnographic approaches to requirements gathering (Suchman 1995).…”
mentioning
confidence: 99%
“…In the following months, the ADR team observed that the VPSI members did not use the service cartography, despite having the tool at their disposal. The evaluation in this iteration was marked by a contextual inquiry [29] the first author conducted with a service manager. In this one-month contextual inquiry, the first author developed a master/apprentice relationship where the service manager was the master.…”
Section: Second Iterationmentioning
confidence: 99%
“…In this one-month contextual inquiry, the first author developed a master/apprentice relationship where the service manager was the master. The idea behind a contextual inquiry is to discover actions as they occur, to allow the service manager to talk about his work as it happens, and not to ask structured questions as in a traditional interview scenario [29]. The goal of this evaluation approach in the ADR project was to learn more about the daily work of a service manager and understand why the service managers did not consult the service cartography.…”
Section: Second Iterationmentioning
confidence: 99%
“…"Protocol Analysis" [17] and the "Apprenticing the Customer" [18], techniques that involves the developer watching the user (in this instance -ophthalmologists) complete various activities such as screening a patient and completing a diagnosis for that patient, were employed. Throughout the activity the ophthalmologist describes to the developer what they are doing, whilst the developer makes notes.…”
Section: User-centred Designmentioning
confidence: 99%